Dynamics of socio-economic indicators development of federal districts of Russia - N. A. Gerasimenko (Вестник университета, 2022)
The article presents the results of a study of the dynamics of the main indicators of the socio-economic development of the federal districts of Russia for the period 2005–2020, which caused the presence of problems associated with the uneven spatial development of the country and correlated with the standard of living of the population. It is shown that the excessive unevenness of the economic development of regions has the most negative effect on their social condition. As part of the study, the analysis of socio-economic indicators in the context of federal districts was carried out on the basis of statistical data from Rosstat, which ensured their comparability for different periods of observation. Long-term trends have been identified, indicating a steady increase in the level of differentiation of a number of indicators between federal districts. The study allowed us to identify three groups of federal districts of Russia, showing: accelerated growth of indicators of socio-economic development above the average level in Russia; relatively insignificant growth rates; the increasing decline in indicators.